Improving Learning Quality in Elementary Schools through Teacher Professional Competence in the Digital - Annisa, Iut Diyah; Nisa, Choirun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Technology in education is no longer just a wishful thinking. Technology is here to make all the impossibilities that once existed disappear. However, its use has not been able to reach everyone. Many have encountered obstacles in accessing it. Lack of knowledge about technology, resistance to change, lack of technology facilities and inadequate school infra-structure, digitalization gap, security and privacy, to the problem of distraction. The purpose of this study is to 1) analyze the condition of professional competence of elementary school teachers in the digital era; 2) identify challenges and obstacles faced by teachers in making the quality of learning in elementary schools better through teacher professional compe-tence in the digital era; 3) formulate effective strategies in making the quality of learning in elementary schools better through teacher professional competence in the digital era. Methodology: The type of research used is qualitative research. Results: Word The results of the study, namely 1) the condition of the professional competence of digital era teachers at Mi Muhammadiyah Kertonatan is currently in good condition with the training of operating technological devices for teachers; 2) there are 3 challenges and obstacles faced by teachers at Mi Muhammadiyah Kertonatan in making the quality of learning better through the professional competence of teachers in the digital era, namely teachers with more senior age often have difficulty in operating technological devices, demands in educating Gen Z with critical thinking characteristics, and the limited availability of technological devices; 3) there are 5 effective strategies in making learning quality in elementary schools better through teachers' professional competence in the digital era, namely continuous training or workshops, technology integration, collaboration between teachers, parental involvement, and flexible curriculum development.